Synthesis and characterization of advanced bio-carbon materials from Kraft lignin with enhanced CO2 capture properties. Issue 3 (June 2022) - Li, Mengbin; Liu, Xin; Sun, Chenggong; Stevens, Lee; Liu, Hao
Abstract: Biomass-derived porous carbons have received enormous attention for CO2 capture in post-combustion scenarios owing to their wide availability, excellent physicochemical stability, and cost-effective preparation. Here, a series of advanced bio-carbon materials were successfully prepared by using the underutilized industrial by-product Kraft lignin as precursor via a facile chemical activation process. Both the textural and surface properties of the bio-carbons were found to be highly tailorable by tuning the activation temperature, KOH/lignin ratio and pre-oxidation treatment. It was found that the Kraft lignin-derived carbons were exceedingly ultra-microporous with ultra-microporosity accounting for up to 92% of total micropores, while the carbons prepared with pre-oxidation treatment were uniquely characterised by distinctive hierarchical micro-mesoporous structures. Applying the Kraft lignin-derived carbons for CO2 adsorption demonstrates that at a CO2 partial pressure of 15 kPa, rarely obtainable CO2 adsorption capacities of 3.29 mmol/g at 0 °C and 2.01 mmol/g at 25 °C were achieved for the carbon prepared at 600 °C. Advanced characterizations confirm that the unique desirable combination of textural properties and surface chemistry, which favours the intercalation of potassium in the form of surface extra-framework K + ions, underpinned the extraordinary CO2 adsorption performance and high CO2 /N2 selectivity (up to 38) of the prepared carbons especially at low CO2 partial pressures. The results indicate that the unique three-dimensional aromatic structures of the lignin provide the matrix for the liable development of the well-defined ultra-microporosity at high levels. Our work provided a promising strategy for valorization of Kraft lignin as a precursor for producing advanced carbon materials. Graphical Abstract: ga1 Highlights: Advanced lignin-based carbons were prepared via a facile chemical activation process. The bio-carbons have highly developed ultra-microporous structure (< 0.7 nm). Superior CO2 uptake of 2.01 mmol/g were achieved at low CO2 partial pressure of 15 kPa and 25 °C. Both surface chemistry and ultra-micropores contribute to the low-pressure CO2 adsorption.